Spontaneous grafting of nitrophenyl groups on amorphous carbon thin films: A structure-reactivity investigation - COLAVITA, PAULA (My University, 2012)
Amorphous carbon materials find numerous applications in diverse areas ranging from implantable biodevices to electronics and catalysis. The spontaneous grafting of aryldiazonium salts is an important strategy for the modification of these materials, and it is widely used to display a range of functionalities or to provide anchoring groups for further functionalization. We have investigated the spontaneous attachment of 4-nitrobenzenediazonium salts from aqueous solutions onto amorphous carbon materials that differ in their sp2 content, with the aim of understanding to what extent bulk composition affects rates and yields of aryldiazonium adsorption at the carbon/solution interface. Amorphous carbons were deposited in the form of thin films via reactive magnetron sputtering and were characterized using a combination of Raman, infrared, UV-vis, and X-ray photoelectron spectroscopy to determine their sp2 content. Attenuated total internal reflection Fourier transform infrared spectroscopy (ATR-FTIR) was used to monitor in situ and in real time the aryldiazonium adsorption process at the carbon/solution interface. These measurements demonstrate that rates and yields of adsorption for the same aryldiazonium salt increase nonlinearly vs sp2 concentration. Studies of aryldiazonium salt grafting as a function of time carried out ex situ via cyclic voltammetry showed that the amorphous carbon film with highest sp2 content displays significantly lower grafting yields than glassy carbon, a material with 100% sp2 content. Intercalation experiments using 4-nitrobenzylamine suggest that the difference in relative density of graphitic edge planes exposed at the carbon surface is in excellent agreement with the observed relative grafting yields. We discuss the implications of these results for the development of structure/reactivity relationships that can be leveraged for understanding the surface chemistry of disordered carbon materials.
PUBLISHED
Keywords: Diazonium; Nitrophenyl; P-nitrobenzene diazonium; Amorphous carbon; Electron transfer; ATR-FTIR; Nanoscience & Materials